Experimental Study of Thermoelectric Generator as Electrical Source of Impressed Current Cathodic Protection for Ship Hull - Adi Kurniawan; Sutopo Purwono Fitri; Muhammad Fajrul Rahman (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
Impressed Current Cathodic Protection (ICCP) is a method to protect metallic material such as ship hull from corrosion by using electric current. In this research, a prototype of thermoelectric generator is developed in order to supply the ICCP system. This thermoelectric generator is planned to utilize the exhaust gas from main engine of the ship. Method carried in this research is assembling the prototype of thermoelectric generator followed by conducted experiment to observe the potential energy of the prototype. After that, the required number of thermoelectric generator is calculated to supply the ICCP system to protect the ship from corrosion. The object in this research is live fish carrier “Wellboat” which has 396.08 m2 wetted area. The required voltage and current to protect the ship from corrosion for three years are 16.67 Volt and 2.66 Ampere. Based on the experiment, a prototype of thermoelectric generator can generate 0.34 Ampere and 4.43 Volt, causing the need of 8 series and 4 parallels connection. It can be concluded that the corrosion rate on the ship hull can be decelerated by using impressed current cathodic protection method without needing additional cost or fuel consumption to produce electric energy.